Breeding ecology, feeding of nestlings and nestling development of the Collared Kingfisher (Todiramphus chloris) in the Indian Sundarbans - Deblina Biswas; Kaushik Deuti (Rivista Italiana di Ornitologia - Research in Ornithology, 2025)
Although commonly occurring in many of the mangrove and coastal areas of the world, the breeding habits, nesting behavior, feeding, and development of nestlings of the Collared Kingfisher (Todiramphus chloris) had never been studied before. Our observations on the nesting behavior of this specialized bird shed light on the unique breeding habits of this species. This study was conducted in the Indian Sundarbans, from April to July 2023, by selecting one particular nest-hole at Gosaba Island on an Avicennia alba tree trunk 1.5 meters above the ground. During the middle of May, four eggs were laid, which hatched after 18 days in early June, giving birth to four blind, naked, pink-colored chicks. The development of the chicks was divided into eight stages: neonatal stage, eye-opening stage, growth stage, tail development stage, eye color changing stage, juvenile stage, collar development stage, and fledgling stage. The total time for the chicks to fly took 33 days from hatching. During this period, parents fed them on crabs (70.5%), mudskippers and small fishes (12.2%), insects (11.5%), polychaetes (1.9%), reptiles and amphibians (1.9%), shrimps (1.1%), and mollusks (0.8%). Feeding observations were made for four hours (5:30-9:30 am) in the morning and two hours (4:30-6:30 pm) in the evening, and chicks were fed more food items (hourly) in the mornings than in the evenings. The adults preferred to collect these food items mostly from the muddy substratum near the nest, but at the time of high tide or after heavy rain, they preferred to collect food (like insects, mole crickets, dragonflies, etc.) from agricultural land opposite to the nesting site. However, the effect of low and high tides on the hunting activity of parents was found to be insignificant. This study in the Indian Sundarbans provides comparatively more detailed information on the nesting ecology of the species than studies made earlier in India, Bangladesh, the United Arab Emirates, and the Fiji Islands.